Investigation of Diffusion and Adsorption of Acetone in Building Materials by Dynamic Method - Yılmaz, Şakir; Akosman, Cevdet (Fırat University, 2018)
In this study, diffusion and adsorption behavior of volatile organic compound of acetone on building materials such as perlite plaster, thermal isolation plate plaster and machine plaster were investigated by using one-sided single pellet moment technique. Experimental studies were conducted in a one-sided single pellet Wicke Kallenbach type diffusion/adsorption cell under isobaric conditions. The amount of acetone in the gas phase was measured by GC technique. The zeroth moment analyses showed that the adsorption of acetone on all gypsum plasters used was found to be reversible. The results indicated that the adsorption degree of acetone on the thermal insulation plaster was the lowest value. The acetone adsorption decreased with increasing temperature while the effective diffusivities of acetone increased with increasing temperature in the gypsum plasters. Moreover, the studies revealed that the adsorption process was physical adsorption process and exothermic.